Knowledge, attitude and practice related to HIV/AIDS among students in a local university (2007) - Rahnama, Rozina; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann; Abdul Rahman, Hejar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: HIV/AIDS has emerged as a threat causing significant morbidity and mortality in human societies. The aims of this study was to determine knowledge, attitude and practice (KAP) and factors associated with HIV/AIDS amongs students in Universiti Putra Malaysia (UPM). Methods: A cross-sectional study was carried out in UPM. A two-stage proportionate to size random sampling technique was used. A standardized pre-tested questionnaire was used to collect the data. The data were analysed using SPSS. Results: The respond rate was 92.3%. The majority (57.3%) of the students were female. The overall mean age of the respondents was 22.5 years (95% CI 22.27-22.70) ranging from 18 years to 52 years. The results show that 91% of the respondents did not know that HIV virus can be killed by bleach; 93.9% stated that pregnant women with HIV virus can give the virus to her unborn baby; 90.2% believed a woman can get HIV if she has unprotected sex with a man; and 93.5% considered that having sex with more than one partner can increase a person’s chance of being infected with HIV virus. The majority (53%) were not willing to care for an HIV infected person in their own house. Only 19.5% of all the students claimed that they will inform their partners or family if diagnosed positive for HIV infection. The majority (93%) approved screening for HIV as a prerequisite for marriage. Only 2.2% of the respondents had multiple sexual partners and 5.4% of the respondents have had sexual intercourse before marriage. About 82.3% of the respondents believed in the used of condom as a means to prevent transmission of HIV. However, of those who were experiencing sexual intercourse with an unmarried partner, only 29.8% used condoms. Conclusion: The level of knowledge related to HIV/AIDS was not satisfactory. It is recommended that a peer educational programme on HIV/AIDS prevention be implemented.